2009
DOI: 10.1007/s10709-008-9343-x
|View full text |Cite
|
Sign up to set email alerts
|

CARE1, a TY3-gypsy like LTR-retrotransposon in the food legume chickpea (Cicer arietinum L.)

Abstract: We report a Ty3-gypsy like retrotransposon CARE1 (Cicer arietinum retro-element 1) in chickpea (Accession no. DQ239702). This 5,920-bp AT-rich (63%) element carries 723-bp 5'-LTR and 897-bp 3'-LTR flanking to an internal region of 4,300-bp. The LTRs of CARE1 show 93.9% nucleotide identity to each other and have 4-bp (ACTA) terminal inverted repeats. A 17-bp potential tRNA(met) primer binding site downstream to 5'-LTR and a 13-bp polypurine tract upstream to 3'-LTR have been identified. The order of characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The Ty3-gypsy spot represented a new appearance in both chickpea lines, whereas the differences in the B3-domain protein were related to differential amount between treatmentsin 'CA336.14.3.0', but new appearance in M + FM treatments in 'ICC 14216 K'. Retrotransposons, a class of transposable elements that encode reverse transcriptase and propagate like retroviruses via a RNA intermediate, are activated by a variety of biotic and abiotic stresses [38]. B3 DNA binding domains are shared by numerous plant-specific transcription factors, including those involved in transcription regulated by auxins and other phytohormones [39].…”
Section: 4mentioning
confidence: 99%
“…The Ty3-gypsy spot represented a new appearance in both chickpea lines, whereas the differences in the B3-domain protein were related to differential amount between treatmentsin 'CA336.14.3.0', but new appearance in M + FM treatments in 'ICC 14216 K'. Retrotransposons, a class of transposable elements that encode reverse transcriptase and propagate like retroviruses via a RNA intermediate, are activated by a variety of biotic and abiotic stresses [38]. B3 DNA binding domains are shared by numerous plant-specific transcription factors, including those involved in transcription regulated by auxins and other phytohormones [39].…”
Section: 4mentioning
confidence: 99%
“…In chickpea, the CARE1 LTR retrotransposon, from the Gypsy superfamily, showed that 5′ LTR was inactive in a heterologous plant under normal and tissue culture conditions, indicating that CARE1 cis-elements might be hindered in the recruitment of transcription factors to the promoter (Rajput and Upadhyaya 2009). The promoter region of the hAT superfamily LTR retrotransposon in Saintpaulia species showed that tissue culture-derived progeny elicit retrotransposon excision, which, in turn, alters the expression levels of flavonoid, 3′, 5′-hydroxylase (F3′F5′H) and flower color in Saintpaulia (Sato et al 2011).…”
Section: Role Of Ltr Retrotransposons In Crop Plantsmentioning
confidence: 99%
“…Given the activity of RTNs in driving genome diversification, RTN-based marker methods appear attractive to be used in chickpea. The sequence of the CARE1, a TY3-gypsy like LTR-RTN, has been identified in C. arietinum (RAJPUT and UPADHYAYA, 2009). Also, several RTN families in legumes closely related to chickpea have been sequenced including TPS family in Pisum sativum (PEARCE et al, 2000), LORE1 and LORE2 in Lotus japonicas (MADSEN et al, 2005;FUKAI et al, 2008) and Tms1Ret1 in Medicago sativa (PORCEDDU et al, 2002).…”
Section: Introductionmentioning
confidence: 99%